Arbovirus persistence in North-Western Europe: Are mosquitoes the only overwintering pathway? - Rody Blom; Maarten J.J. Schrama; Jeroen Spitzen; Babette F.M. Weller; Anne van der Linden; Reina S. Sikkema; Marion P.G. Koopmans; Constantianus J.M. Koenraadt (One Health, 2023)
In some areas in temperate Europe, genomic analyses of mosquito-borne virus outbreaks have revealed the presence of similar virus strains over several years, indicating local overwintering of these viruses. However, it remains unclear how mosquito-borne viruses can persist in winter, when conditions are generally unfavourable for virus circulation. One of the presumed routes of virus persistence is via diapausing mosquitoes. Here, we set out to study whether arbovirus persistence of West Nile virus (WNV), Usutu virus (USUV) and Sindbis virus (SINV) occurs in diapausing mosquitoes in the Netherlands. To this end, mosquito collections were carried out in the winter of 2020 and 2021, in hibernacula located in two areas with previously observed WNV and/or USUV activity. In total, we collected 4200 mosquitoes belonging to four species (Culex pipiens, Culiseta annulata, Anopheles maculipennis s.l., and Culex territans), which were pooled in 490 monospecific pools. These pools were subjected to WNV-, USUV- and SINV-screening using a multiplex real-time RT-PCR assay. All mosquito pools tested negative for the presence of WNV, USUV and SINV RNA. Consequently, we did not find evidence of arbovirus persistence in diapausing mosquitoes in the Netherlands, even though USUV and WNV have re-appeared in birds and/or mosquitoes during the summer seasons of 2020–2022. Concluding, given the persistence of USUV and WNV in the Netherlands and SINV in other temperate regions, this study highlights the importance of further research on (alternative) arbovirus overwintering routes.